AN EFFICIENT AND REPRODUCIBLE TISSUE CULTURE PROCEDURE FOR CALLUS INDUCTION AND MULTIPLE SHOOTS REGENERATION IN GROUNDNUT (Arachis hypogaea L.) - N. Ahmad; M. R. Khan; S. H. Shah; M. A. Zia; I. Hussain; A. Muhammad; G. M. Ali (Journal of Animal and Plant Sciences, 2020)
This study was carried out to optimize in vitro regeneration system of groundnut through tissue culture technology that can provide good environment in terms of food security. The two varieties of groundnut (Golden and BARI 2001) were used and an effective in vitro regeneration system was established for selecting the best responsive variety to tissue culture using embryo as an explant sources. MS media having 5.5 mg/l BAP and 1.5 mg/l NAA was found to be best by producing the highest callus induction frequencies (86 & 78%) in Golden and BARI 2001, respectively. Similarly, the maximum multiple shoots/ plant (9 & 6) with optimum length of shoots (4.8 & 4.1 cm) was obtained with the application of 4 mg/l BAP along with 1 mg/l NAA and 1.1 mg/l TDZ in Golden and BARI 2001, respectively. In case of roots initiation, the highest root frequency (90 & 76%) having optimum roots/shoots (8.3 & 6.2) and substantial root length (8.1 & 7.0 cm) was obtained in Golden followed by BARI 2001 variety on MS media having 1 mg/l phytohormone IBA. Results showed that callus and multiple shoot induction and in vitro rooting, varied with different hormonal combinations in the media and the genotype that might be due to genetic variations between the varieties. This study delivers a base line for efficient in vitro propagation and genetic transformation in elite groundnut genotypes for desirable characteristics.
Keywords: Callus induction; Embryo slices; Genetic transformation; Multiple shoots; Plant growth regulators